Factors Affecting The Level Of Financial Literation In College Student - Havea Prama Silta; Ida Miharti (Universitas Negeri Gorontalo, 2020)
This research is conducted to obtain empirical evidence that there are influences on financial literacy. The sample used in this research is college student in Faculty of Economic Andalas University. A regression analysis is used to test the hypothesis. Hypothetical test results show that there are no influences of gender, department, parent’s income and parent’s education on financial literacy, but only the year entry has an influence on financial literacy.